2009
DOI: 10.1007/s11552-009-9220-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of the Carpal Tunnel

Abstract: Although carpal tunnel release is one of the most commonly performed procedures in the USA, the morphology of the carpal tunnel as determined previously in the literature has been questioned. Previous methodology has been questioned for accuracy by recent studies. The purpose of this study was to perform a morphological analysis of the carpal tunnel and correlate carpal tunnel and hand dimensions. The carpal tunnels of ten cadaveric specimens were emptied of their contents and a silicone cast of the carpal tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 15 publications
1
29
2
Order By: Relevance
“…This has been questioned through more recent studies. It was reported that neither the width, nor depth, nor cross-sectional area changes significantly along the length of the carpal tunnel (6,28). The definitions of proximal and distal extends of the carpal tunnel might be responsible for this argument since the reported length of the carpal tunnel is 12.7 ± 2.5mm in one study and 21.7 ± 6.05 in the other (7,28).…”
Section: Demircay E Et Al: Anatomic Variations Of the Median Nervementioning
confidence: 89%
“…This has been questioned through more recent studies. It was reported that neither the width, nor depth, nor cross-sectional area changes significantly along the length of the carpal tunnel (6,28). The definitions of proximal and distal extends of the carpal tunnel might be responsible for this argument since the reported length of the carpal tunnel is 12.7 ± 2.5mm in one study and 21.7 ± 6.05 in the other (7,28).…”
Section: Demircay E Et Al: Anatomic Variations Of the Median Nervementioning
confidence: 89%
“…Evaluation of the dimensions of the carpal tunnel has been inadequately addressed in the literature on CTS, as most previous studies evaluated the dimensions of the carpal tunnel in normal individuals and not in CTS patients. These studies, which were performed on healthy patients or cadavers, employed either computed tomography (CT) or magnetic resonance imaging (MRI), or used a silicon cast to fill the carpal tunnel to measure these dimensions (Bower et al 2006;Mani et al 2011;Pacek et al 2010;Widgerow et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Within the carpal tunnel complex, the transverse carpal ligament (TCL) along with the hypothenar and thenar muscles are important in the stability of the carpus and form the roof of the carpal tunnel. The volar boundary of the carpal tunnel commonly referred to as the flexor retinaculum comprises a strong band of connective tissue consisting of the proximal thin antebrachial fascia, the middle thick TCL and the most distal aponeurosis between the hypothenar and thenar musculature (Brooks et al, 2003;Cobb et al, 1993;Pacek et al, 2010b). Anatomically, the TCL attaches to the carpal bones distally and proximally.…”
Section: Introductionmentioning
confidence: 99%